Analysis Of Risk Factors Affecting Hypertension Disease In The Jayaloka Village Area, Empat Lawang Regency - Agustina, Elvira Eka; Andriani , Melda; Wulandari, Suci; Kartini, Aprilia; Sari , Winda Puspa; Aprianti, Delta; Rohani, Tuti; az, Danur (Universitas Dehasen Bengkulu, 2025)
Hypertension, or high blood pressure, is one of the leading causes of death and disability worldwide. This disease has become a growing global health problem, especially in developing countries, including Indonesia. Hypertension often shows no symptoms in its early stages, earning it the nickname